Genetic divergence and path analysis in wheat cultivars under heat stress - Silva Oliveira, Carlos Eduardo da [UNESP]; Andrade, Agner de Reitas; Zoz, Andre [UNESP]; Sobrinho, Renato Lustosa; Zoz, Tiago (Univ Federal Goias, 2020)
One of the biggest limitations for the wheat crop expansion to Brazilian tropical regions is the high temperature in the rainy season. This study aimed to select, based on genetic divergence and path analysis, cultivars that tolerate cultivation in the summer (heat stress). Nine wheat cultivars were sown, using a randomized block design with three replications, with plots consisting of 10 rows of 6 m and row spacing of 0.15 m. The highest grain yield and number of ears m(-2) were observed for the CD 150 cultivar and the largest 1,000-grain weight for CD 116. BRS 220, IPR 136, IPR 144 and BRS Pardela had the highest number of sterile spikelets. The highest number of grains per ear was observed for CD 150, CD 116, BRS Pardela, IPR 130 and IPR 85, showing direct effects on grain yield, evidenced by the path analysis. CD 116 and CD 150 were the most productive cultivars and can be considered as possible parents in wheat breeding programs. IPR 85, CD 116, CD 108 and CD 150 showed a greater tolerance to high temperatures.
Keywords: Triticum aestivum; genotypic correlations; high-temperature tolerance; wheat crop expansion